Jacobsthal Trigonometric Functions - Pakapongpun, Apisit; Chailangka, Natdanai (IndoMS, 2025)
Jacobsthal numbers satisfy a second order homogeneous recurrence relation J_n=J_n-1+2J_n-2 where J_n denotes the n^th Jacobsthal number. In this paper, the Jacobsthal sine, cosine, tangent and cotangent are defined, and some identities of Jacobsthal trigonometric functions are provided.